The tamarind forest: an augmented virtuality experience - Polydorou, Doros (My University, 2021)
The tamarind forest is a virtual reality (VR) installation that explores shifts of perception through a somatic experience in a virtual space. As part of a larger show (kimosphere no.4) that explored immersion and an entwinement of real and virtual spaces, The Tamarind forest experiments with augmented virtuality and invites the audience to pay attention to their physical body while taking a journey through a virtual forest. This paper describes the piece, the technology and the design process as well as the main takeaways and reflections.
Keywords: Virtual reality; Augmented virtuality; Digital performance; Site-specific performance; Digital embodiment